Penerapan Metode Evaluation based on Distance from Average Solution (EDAS) dalam Optimalisasi Layanan dan Pemasaran Coffeeshop - Yerik Afrianto Singgalen (Journal of Computer System and Informatics (JoSYC), 2023)
Business owners of coffee shops that fall under the Micro, Small, and Medium Enterprises (MSMEs) employ marketing methods to attract more clients to satisfy the demands and preferences of coffee enthusiasts. However, consumer purchasing behavior demonstrates the difficulty in evaluating marketing performance. In light of this, this study employs the Distance from Average Solution Evaluation Method (EDAS). Meanwhile, coffee shop business brands observed and used as alternatives in this study are Coffee Tanem, 1915 Koffie-Huis, Friends of Coffee Salatiga, Dusk Koffie Salatiga, and Street Side Coffee Salatiga. The results of this study show that the EDAS method can be used to optimize coffee shop business services and marketing as a strategic step in strengthening and improving the performance of the coffee shop business or business. In the context of testing the EDAS decision model, each alternative is assigned a random code (A1-A5). Coffee varieties (C1), aroma and roasted level (C2), serving technique variants (C3), beverage prices (C4), and coffeeshop locations (C5) are often employed as criteria, with categories C1–C3 representing advantages, and C4–C5 representing expenses. Based on the EDAS method's calculation results, it can be seen that the top-ranking coffee shops are those that offer a variety of coffee bean varieties (robusta and arabica), various aromas, and roasted levels (light, medium, dark), various serving methods using espresso machines and manual brew, affordable drink prices, and strategically located coffee shops with enough parking. Thus, it is advised that coffee shop business experts assist in improving capital capabilities and business performance and optimize marketing mix components in STP (Segmenting, Targeting, Positioning) marketing strategies to increase trust, sales volume, consumer satisfaction, and loyalty.